Quantitative analysis of "Δl = ls − lg" to coherent random lasing in solution systems with a series of solvents ordered by refractive index. Issue 100 (14th October 2016) - Yin, Leicheng; Liang, Yunyun; Yu, Bo; Wu, Yeping; Ma, Jiajun; Xie, Kang; Zhang, Wei; Zou, Gang; Hu, Zhijia; Zhang, Qijin
Abstract : Random laser action affected by solvents ordered by refractive index in solution system. Abstract : This work systematically illustrated the effects of solvents on random lasing in active scatterer solution systems. The scatterer, N, N ′-di[3-(isobutyl polyhedral oligomeric silsesquioxanes)propyl]perylene diimide (DPP), was chemically synthesized from gain group perylene diimide (PDI) and scattering group polyhedral oligomeric silsesquioxanes (POSS) at a mole ratio of 1 : 2 through chemical bonding. Random lasing action was detected in such solutions with a series of solvents ordered by refractive index (RI), from which it was found that solution systems with larger RI solvent facilitate boosting of random laser (RL) for a suitable "Δ l = l s − l g " ( l s > l g ). There are two potential situations for solvents with smaller RI: in one, a small RI difference between scatterers and surroundings results in extremely large l s, and the extremely large Δ l in these samples means that there is no observation of random lasing; in the other, there is increased l g as characterized by UV-Vis spectroscopy, although the l s remains almost unchanged for the large RI fluctuations between scatterers and surroundings, resulting in smaller Δ l with no detection of random lasing as the laser pumping energy cannot compensate for the gain loss. Results from this work will aid in quantitatively judging the necessary condition of "Δ l = l s − l g " to RL in solutions, and aid in designing suitable solution systems to boost RL.